The Effect of Different Salinity on Density and Carotenoid Content Dunaliella salina - Nisa, Khairun; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Perikanan dan Kelautan, 2020)
Dunaliella salina is a microalga containing carotenoids. Carorenoids have a role in the absorption of light for photosynthesis, carotenoids also function in coloring for aquaculture animals. Carotenoids is influenced by a variety of environmental factors, such as salinity. This study aims to get the best salinity in increasing the density and carotenoid content of D. salina. The research method used is an experimental method using a Completely Randomized Design (CRD) consisting of One factor with four improvements, to reduce the level of error then repeated three times. This research was conducted in March to May 2019 in the Laboratory Natural Feed Brackish Water Aquaculture Development Center (BBPBAP) located in Jepara Bulu Village, Jepara District, Jepara Regency, Central Java Province. Carotenoid analysis done in the Lab. Primary Chem-Mix located in Kretek, Jambidan, Banguntapan, Bantul, Yogyakarta. The treatment in this study included P1 (salinity 20 ppt), P2 (salinity 30 ppt), P3 (salinity 40 ppt) and P4 (salinity 50 ppt). The results showed that the cell ratio was highest filled in P2 with a concentration reaching 664.86 x 104 cells/mL and contents the highest carotenoid in P4 is 1.4769 μg/mL.